2009
DOI: 10.1088/0957-4484/20/8/085201
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube thin film transistors based on aerosol methods

Abstract: We demonstrate a fabrication method for high-performance field-effect transistors (FETs) based on dry-processed random single-walled carbon nanotube networks (CNTNs) deposited at room temperature. This method is an advantageous alternative to solution-processed and direct CVD grown CNTN FETs, which allows using various substrate materials, including heat-intolerant plastic substrates, and enables an efficient, density-controlled, scalable deposition of as-produced single-walled CNTNs on the substrate directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 43 publications
1
45
0
Order By: Relevance
“…[86] Accordingly, CNTs with Y-junctions (which have a large junction area) have a much better electrical performance than do X-junctions (which have a small junction area and therefore a high contact resistance), showing an increase of carrier mobility from 4 to 35 cm 2 V −1 s −1 . [137,174] It was also found that the effective length of CNTs in the current flow direction of TFTs is short for X-junction dominated networks, and thus, the number of junctions in the current path and resistance of the network are increased.…”
Section: Factors Affecting Tft Performancementioning
confidence: 98%
“…[86] Accordingly, CNTs with Y-junctions (which have a large junction area) have a much better electrical performance than do X-junctions (which have a small junction area and therefore a high contact resistance), showing an increase of carrier mobility from 4 to 35 cm 2 V −1 s −1 . [137,174] It was also found that the effective length of CNTs in the current flow direction of TFTs is short for X-junction dominated networks, and thus, the number of junctions in the current path and resistance of the network are increased.…”
Section: Factors Affecting Tft Performancementioning
confidence: 98%
“…While there have been many reports of synthesis of CNTs using AACVD, surprisingly there are only few reports of their application in real devices. [22,23] Here, we grew CNTs on to steel substrates and studied their performance in supercapacitors, which exhibited a high geometric capacitance of 3.4 mF cm À2 . Steel is the substrate of choice for two main reasons.…”
Section: Introductionmentioning
confidence: 99%
“…In these structures, CNTs act as transparent electrodes replacing In 2 O 3 :Sn (ITO) or semitransparent metal layers, and promoting an increase of the collection area for current carriers photogenerated in semiconductor. At the same time, the optical and conduction properties of the network layers made of SWCNTs were shown to depend both on technology of CNT layer formation and deposition on the substrate as well as on the structure and adhesion properties of substrate [1, 2,[5][6][7][8]. So, the elaborated by us method of SWCNT nanolayer deposition on the Si surface modified with poly(vinylpyridine) (PVP) for Au/n-Si photovoltaic structures [5] should be verified in the case of other structures.…”
Section: Introductionmentioning
confidence: 99%